Students Learning Obstacles Related to Mathematical Literacy Problem: A Systematic Literature Review - Rayhan, Nabila Cynthia; Juandi, Dadang (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to describe the results of research on learning obstacles related to mathematical literacy problems. This research uses the Systematic Literature Review (SLR) method. The sample consisted of 13 studies on learning obstacles related to mathematical literacy problems published from 2017 to March 2023. The results of this study were reviewed based on the publication media, year of publication, level of study, research location, materials used in the study, and results on learning obstacle research related to mathematical literacy problems. Using the SLR method, It was found that the most research was published in the Repository UPI while the most articles were published in SINTA 3, the highest number of published research in 2022, the highest level of education is carried out at the junior high school level, the location was predominantly carried out in Java Island, Space and Shape content and Uncertainty and Data content was most widely used in learning obstacle research related to mathematical literacy problems, and in terms of three types of learning obstacles namely, ontogenic obstacles, didactical obstacles, and epistemological obstacles. It was detected that epistemological obstacles were found in as much as 100% throughout the study, while ontogenic obstacles were found in as much as 69%, and didactical obstacles were found in much as 46%.